Pengembangan Pembelajaran Mobile Learning Berbasis Kearifan Lokal: Analisis Bibliometrik - ida mawaddah; Sudarsono Sudarsono; Burhanuddin Burhanuddin (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
This study aims to reveal education as part of a conscious effort to advance human life with local cultural characteristics. The development of media in the world of learning can help students easily understand the meaning of philosophy, quote moral messages, motivate themselves, develop themselves and support sustainable development according to the character of the Indonesian nation. To understand the development of the bibliometric approach incorporating network analysis from the top internal citations to describe the development of historiography of research domains including e-learning, multimedia learning multiplatform application technology, local wisdom and digital literacy, problem solving. The conclusions of the subgroups and the list of articles are important becausecontribute comprehensive methods to enable rapid understanding of the overall research development.